Pendampingan Pengenalan Microsoft Mathematics untuk Meningkatkan Minat Siswa terhadap Matematika - Gregoria Ariyanti; Ana Easti Rahayu Maya Sari (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
One of measure of student success is their learning achievement. Among the subjects that are not liked by many students that is mathematics. During the Covid-19 pandemic, with the presence of information technology, the learning process began to be carried out online. Not all students can understand the learning that is carried out online, so it is necessary to seek learning applications that can help students to understand the lessons, especially mathematics. Community service activities carried out are in the form of theoretical and practical assistance using the Microsoft Mathematics application to help students to understand the completion of Mathematics problems. The community service activity was carried out in a group of XII grade students of SMAK Santo Bonaventura Madiun who had not fully use of mathematics applications. The results obtained from this community service were an increase in student interest in mathematics by 12% after knowing and using the Microsoft Mathematics application in solving math problems. It can be concluded that the role of information technology can increase student interest in learning so that it affects learning outcomes. Salah satu ukuran keberhasilan siswa adalah prestasi belajarnya. Diantara mata pelajaran yang tidak banyak disukai siswa yaitu matematika. Pada masa pandemi Covid-19, dengan adanya teknologi informasi, proses pembelajaran mulai dilakukan dalam jaringan. Tidak semua siswa bisa memahami pembelajaran yang dilakukan dalam jaringan, sehingga perlu diupayakan aplikasi pembelajaran yang dapat membantu siswa memahami pelajaran, khususnya matematika. Kegiatan abdimas yang dilakukan berupa pendampingan secara teori dan praktek menggunakan aplikasi Microsoft Mathematics dalam membantu siswa memahami penyelesaian soal matematika. Kegiatan abdimas dilakukan pada kelompok siswa kelas XII SMAK Santo Bonaventura Madiun yang belum memanfaatkan aplikasi matematika dengan maksimal. Hasil yang diperoleh dari abdimas ini yaitu adanya peningkatan minat siswa terhadap matematika sebesar 12% setelah mengenal dan menggunakan aplikasi Microsoft Mathematics dalam menyelesaikan soal matematika. Dapat disimpulkan bahwa peranan teknologi informasi dapat meningkatkan minat siswa untuk belajar sehingga berpengaruh terhadap hasil belajarnya.